Particle deflection and plate-out dynamics in a helium stream - Steyn, Hermanus Johannes (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2009.